The effects of 8 weeks of multi-directional movement training combined with balance training on the change of direction of young table tennis players - Chen, Qianqian; Li, Yanfei; Heng, Xinchen; Zhao, Lei; Wu, Bin (Frontiers in Physiology, 2025)
BackgroundChange of direction (COD) skills are crucial for athletic performance in sports such as table tennis. Improving COD can enhance overall agility and responsiveness during competition.ObjectiveTo investigate the effects of an 8-week multi-directional movement training combined with balance training on the COD performance of young table tennis players.MethodsThirty young table tennis players from the same team were randomly assigned to two groups: the multi-directional movement training combined with the balance training group (MB, n = 15) and the control group (CON, n = 15). The MB group underwent balance training on unstable surfaces, while the CON group performed the same balance exercises on stable ground. Both groups participated in the same multi-directional movement training program, which was conducted three times a week with 24–48 h of recovery between sessions for a duration of 8 weeks.ResultsSignificant group effects were observed in the modified agility test, non-dominant leg, dominant leg, and push block side lunge right test (p < 0.05). No significant group effects were found for the hexagon agility test, 3 m side slide test, A-movement test, or the whole table variable speed pendulum test (p > 0.05). Significant time-by-group interactions were noted for all variables (p < 0.05), indicating that improvements over time differed between the MB and CON groups. In the MB group, significant improvements were observed across all tests post-intervention, with high effect sizes (Partial η2 values ranging from 0.361 to 0.815). In contrast, the CON group showed significant time effects in only a few tests, including the 3 m side slide test, A-movement test, modified agility test, and push block side lunge right test (p < 0.05), with no significant time effects for other variables.ConclusionThis study aimed to explore whether multi-directional movement training, when combined with balance exercises, could improve COD skills in young table tennis players. The results will inform future training strategies for enhancing agility and movement efficiency in table tennis athletes.